The Correlation Between Interpersonal Communication and Optimism With Adversity Quotient for Non-Permanent Employees of the Medan Tourism Polytechnic - Anggreani, Christina; Effendy, Sjahril; Hasanuddin, Hasanuddin (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to determine The Correlation between Interpersonal Communication and Optimism with Adversity Quotient for Non-Permanent Employees of the Medan Tourism Polytechnic. The hypothesis proposed is there is a correlation between Interpersonal Communication and Optimism with Adversity Quotient for Non-Permanent Employees of the Medan Tourism Polytechnic. The sample in this study amounted 65 respondents. The sampling technique using total sampling. The data collection method is a Likert scale of interpersonal communication, optimism, and adversity quotient. Data analysis uses multiple linear regression analysis models. The results of this study are: 1. There is a positive and significant correlation between interpersonal communication and adversity quotient. This is indicated by the correlation coefficient (R) = 0.407 with p = 0.001 <0.05. Based on the results of this study, the first proposed hypothesis was declared accepted. 2. There is a positive and significant correlation between optimism with adversity quotient. This is indicated by the correlation coefficient (R) = 0.461 with p = 0.000 <0.05. Based on the results of this study, the second proposed hypothesis was declared accepted 3. There is a positive and significant correlation between interpersonal communication and optimism with adversity quotient. This is indicated by the correlation coefficient (R) = 0.626 with p = 0.000 <0.05. Based on the results of this study, the third proposed hypothesis was declared accepted. It is known that the subjects of this study, Non-Permanent Employees of the Medan Tourism Polytechnic have high interpersonal communication, low optimism, and low adversity quotient.